Low-Temperature Production of Genuinely Amorphous Carbon from Highly Reactive Nanoacetylide Precursors - Ken Judai; Naoyuki Iguchi; Yoshikiyo Hatakeyama (Journal of Chemistry)
Copper acetylide is a well-known explosive compound. However, when the size of it crystals is reduced to the nanoscale, its explosive nature is lost, owing to a much lower thermal conductance that inhibits explosive chain reactions. This less explosive character can be exploited for the production of new carbon materials. Generally, amorphous carbon is prepared by carbonization of organic compounds exposed to high temperature, which can induce partial crystallization in graphite. In this work, we present a new method in which the carbonization reaction can proceed at a lower annealing temperature (under 150°C) owing to the highly reactive nature of copper acetylide, thus avoiding crystallization processes and enabling the production of genuinely amorphous carbon materials.